Antegrade Versus Retrograde Technique for Fixation of Scaphoid Waist Fractures: A Comparison of Screw Placement - Lucenti, Ludovico; Lutsky, Kevin F.; Jones, Christopher; Kazarian, Erick; Fletcher, Daniel; Beredjiklian, Pedro K. (Journal of Wrist Surgery, 2020)
Background Scaphoid waist fractures are often treated using headless compression screws using dorsal or volar approaches.Objectives The purpose of this study is to compare differences in screw position using a volar (retrograde) or dorsal (antegrade) approach.Patients and Methods A total of 82 patients were retrospectively evaluated: 41 treated with a volar and 41 with a dorsal approach were selected. Postoperative radiographs were reviewed by three observers who rated screw location in the proximal pole, waist, and distal pole.Results Thirty-four patients (83%) in the antegrade group had central screw placement in the waist of the scaphoid in posteroanterior and lateral planes compared with 14 (34.9%) in the retrograde group (p < 0.05). For the antegrade group, the screw was central in 217 of 246 zones (88.2%) compared with 127 of 246 (51.6%) in the retrograde group (p < 0.05).Conclusions The dorsal antegrade approach appears to allow the surgeon to achieve central screw placement along all three scaphoid regions.Level of Evidence This is Level III study.
Keywords: antegrade approach; retrograde approach; scaphoid screw fixation; scaphoid waist fracture